Morphological Identification of Helminth Parasites in Gallus gallus domesticus in Lucknow, U.P., India - Kamal Jaiswal,; Suman Mishra,; Vandana, (The Bioscan, 2026)
Poultry farming is one of the most developed, profitable, and intensively practiced forms of animal production. Gastrointestinal worms are well-known parasites of poultry birds responsible for decreasing poultry productivity. So the microscopic study revealed the possibility of differentiating helminthic parasites. Cestodes and nematodes were collected from the domestic fowl (Gallus gallus domesticus) in Lucknow, Uttar Pradesh. Light microscopy was used for the detailed identification of helminths. In total, 300 gastrointestinal tracts were inspected for helminths between July 2023 and June 2024. The helminths that were gathered were identified using Yamaguti's (1961) and Soulsby's (1982) keys and descriptions. In Lucknow, a significant percentage of helminth infections (95%) were found in household poultry. Two cestode species (Raillietina tetragona & Cotugnia diagnopora) and one nematode species (Ascaridia galli) were found throughout the investigation. The majority of the helminths were retrieved from the small intestine, followed by the caecum. According to this study, helminths cause major issues for domestic chickens which reduce productivity. So suitable control measures on the basis of study must be developed to improve output.